Infection in Critically Ill Pediatric Patients on Continuous Renal Replacement Therapy. Issue 5 (May 2017) - Santiago, Maria J.; López-Herce, Jesús; Vierge, Eva; Castillo, Ana; Bustinza, Amaya; Bellón, Jose M.; Sánchez, Amelia; Fernández, Sarah
Introduction: Continuous renal replacement therapies (CRRT) are frequently used in critically ill children and may increase the risk of infection. However, the incidence, characteristics and prognosis of infection in critically ill children on CRRT have not been studied. Methods: Data from a prospective, single-center register of critically ill children treated with CRRT was analyzed. Results: 55 children (40% under 1 year of age) were treated with CRRT between June 2008 and January 2012; 43 patients (78.2%) presented 1 or more infections. The most common condition of patients requiring CRRT was heart disease (69%). Infection occurred a median of 11 days after the initiation of CRRT (IQ range: 4 to 21 days). A total of 21 patients (48.8 %) developed 1 infection, 7 (16.2%) developed 2 infections and 15 (34.9%) developed 3 or more infections. The most frequent infection was catheter-related bacteremia, with no differences in catheter location. CRRT duration longer than 4.5 days was the only risk factor for infection. Patients with infection had a longer length of stay (LOS) in the Pediatric Intensive Care Unit (PICU) than patients without it (37.8 vs. 17.6, p = 0.019), but there were no differences in mortality (30.2% vs. 33.3%; p = 0.84). Conclusions: Infection rate is high in critically ill children treated with CRRT. More than 4 days of CRRT increases the risk of infection. Infection in these patients entails a longer stay in the PICU but did not increase mortality.